The Application of Criminal Sanctions Against the Victims of Narcotics Abuse (Case Study of Decision Number: 193/Pid.Sus/2025/PN. Sdn) - Jainah, Zainab Ompu; Ramadan, Suta; Yulistia, Alyaa (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Indonesia has aggressively combated narcotics over the past decade, yet it remains one of the countries with the highest incidence of narcotics offenses, exacerbated by cross-border trafficking. To prevent and eradicate narcotics abuse and illicit trafficking that endanger society, the nation, and the state, Law Number 35 of 2009 on Narcotics was enacted. This law regulates the use of narcotics for medical purposes, health services, and physical and social rehabilitation, and also stipulates sanctions such as imprisonment, fines, rehabilitation, and capital punishment. This study aims to examine the factors that cause offenders to become victims of narcotics abuse and to analyze criminal liability for victims of narcotics abuse based on Decision Number 193/Pid.Sus/2025/PN.Sdn. This research employs a qualitative approach with descriptive analysis. The findings indicate that narcotics abuse is caused by internal factors and external environmental factors, including lack of family attention and support during adolescent development, peer influence, and free social interaction, all of which may lead to narcotics abuse and jeopardize the future of young individuals. Criminal liability for narcotics abusers may be imposed under Article 127 paragraph (1) letter (a) of Law Number 35 of 2009 on Narcotics, with a maximum imprisonment of four (4) years. Therefore, this situation requires an active role of the government in increasing public legal awareness of the dangers of narcotics, as well as community participation in narcotics eradication efforts.